Kajian Etnosains Masyarakat tentang Pembuatan Pupuk Kompos sebagai Alternatif Pupuk Anorganik dengan Memanfaatkan Kotoran Kelelawar di Kawasan Ekowisata Pulau kelelawar Desa Ujung Pasir - Emayulia Sastria; Novinovrita Novinovrita; Dinyah Rizki Yanti Zebua (Symbiotic: Journal of Biological Education and Science, 2024)
This research investigates the use of bat guano compost as an alternative to inorganic fertilizers in organic farming practices in the ecotourism area of Bat Island. Ethno Scientific approach and qualitative research methodology are employed to gain deeper understanding of the knowledge, beliefs, traditional practices, and perspectives of the community regarding compost. Data collection methods involved observations and interviews conducted from May to June 2021. Observational activities were carried out through direct observation of the Ujong Pasir location, which serves as the ecotourism area of Bat Island. Research informants included traditional leaders, village government officials, and the local community. The findings reveal that the community possesses extensive knowledge of compost production from bat guano and perceives it as an environmentally friendly and sustainable solution in agriculture. Their perspectives reaffirm the commitment to organic farming and the need for sustainable agricultural practices. Furthermore, collaboration among the community, farmers, and researchers in the development and enhancement of compost utilization demonstrates significant potential for expanding knowledge and implementing organic farming practices within the community. These findings underscore the importance of cross-sectoral collaboration in supporting sustainable agriculture and environmental conservation in ecotourism areas. Further research is recommended to delve deeper into the technical and social aspects of compost utilization, as well as to formulate more effective strategies for promoting the adoption of organic farming practices within the community.